Penerapan PMR Berbantuan Alat Peraga Obibul Terhadap Hasil Belajar Siswa Pada Materi Operasi Hitung - Usman, Kartin; Takaendengan, Bertu Rianto; Asnani, Asnani (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
The aim of this research is to determine the differences in student learning outcomes taught using the realistic mathematics approach (PMR) assisted by Obibul teaching aids and the learning outcomes of students taught using the direct learning model. The research method used is the experimental method, with a design namely pretest-posttest control group design. Sampling used a random sampling technique from 3 classes, namely classes VII.A, VII.B and VII.C, two classes were selected as samples with a total of 25 students as respondents for each class. Based on the results of the lottery drawing, class VII.B was selected as the experimental class which used a realistic mathematics approach (PMR) assisted by Obibul teaching aids while class VII.A was selected as the control class which used a direct learning model. The instrument used for research is in the form of a description/essay. Hypothesis testing uses the ANCOVA test which produces Fcount = 5.73, which is compared with the value of ð¹table = 3.94 so that ð»0 is rejected. The results of this research concluded that there were differences in the learning outcomes of students who were taught using the realistic mathematics approach (PMR) assisted by Obibul teaching aids and the learning outcomes of students who were taught using the direct learning model.